Adsorption of Fe Metal Ions in Laboratory Wastewater with Chitosan from Fish Scales - Ramadhini, Tri Karimah; Agustina, Tuty Emilia; Fadhlurrahman, M Arif; Nufus, Dian Natasya Alfa; gayatri, Ryaniza (The Journal of Pure and Applied Chemistry Research, 2024)
Laboratory wastewater contains organic compounds and heavy metals, such as iron (Fe), manganese (Mg), chromium (Cr), and mercury (Hg). These pollute the environment, especially the groundwater. One alternative to process laboratory wastewater by using adsorption method. The adsorption method requires an absorbent. The waste from fish scale was reported contains chitosan and can be applied as adsorbent materials. The paper reports our preparation of chitosan from fish scales. Then, it was applied as adsorbent, and studying the effect of chitosan weight / dose, pH, and stirring time for removal of iron metals ion. The best Fe removal percentage of 99.82% was obtained by using the chitosan dose of 2 g and a stirring time of 60 minutes. The pH condition with the highest Fe removal percentage was at pH 4 (99.98%). The optimum condition then applied to laboratory wastewater. The developed strategic was able to meet the standard for water quality according to Minister of Environment Regulation No. 5 in 2014.